2021
DOI: 10.1111/php.13370
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Derived from ADSCs Attenuates Ultraviolet B‐mediated Photoaging in Human Dermal Fibroblasts

Abstract: Stem cell therapies have attracted a lot of attention in the fields of dermatological and esthetic medicine. The paracrine action of stem cells is deemed to play a crucial role in skin treatments. Many reports have demonstrated the beneficial effects of conditioned medium (CM) derived from ADSCs on skin photoaging. However, few reports have presented the application of exosome (Exo) derived from ADSCs in the treatment of photoaging. To clarify the effects of Exo, we collected Exo from the CM of ADSCs and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Several studies have found that ADSC transplantation therapy can reverse scleroderma-induced cutaneous brosis [13,14]. Exosome secretion by ADSCs plays an important role in microenvironmental regulation via delivery of bioinformatics molecule [15,16]. The present study found that ADSC exosome treatment avoids dermal thickening and brosis induced by bleomycin administration.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have found that ADSC transplantation therapy can reverse scleroderma-induced cutaneous brosis [13,14]. Exosome secretion by ADSCs plays an important role in microenvironmental regulation via delivery of bioinformatics molecule [15,16]. The present study found that ADSC exosome treatment avoids dermal thickening and brosis induced by bleomycin administration.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have found that ADSC transplantation therapy can reverse scleroderma-induced cutaneous brosis [16,17]. Exosome secretion by ADSCs plays an important role in microenvironmental regulation via delivery of bioinformatics molecule [18,19]. The present study found that ADSC exosome treatment avoids dermal thickening and brosis induced by bleomycin administration.…”
Section: Discussionsupporting
confidence: 63%
“…There were recently reported studies elucidating that human umbilical cord mesenchymal stem cellderived exosomes (hucMSC-Exo) significantly reduced the expression of collagen and p-Smad2 to alleviate liver fibrosis in vivo [60]. Other than that, MSC-Exo regulated the fibrosis repair of injured endometrium by downregulating Smad signaling pathway, demonstrating that phosphorylation levels of Smad2 were gradually decreased with the increased concentration of exosome in BMSCs and Exo treatment groups [61]. Besides, levels of collagen, α-SMA, and phosphorylation of Smad2/3 were markedly decreased in fibroblasts treated with hucMSC-derived exosomes, suggesting that hucMSC-derived exosomes could inhibit dermal fibroblast-myofibroblast transition by inhibiting the Smad signaling pathway [62].…”
Section: Discussionmentioning
confidence: 99%